2020
DOI: 10.1186/s41983-020-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke sleep disorders in Egyptian patients by using simply administered questionnaires: a study from Ain Shams University

Abstract: Introduction: Stroke is a leading cause of disability worldwide with grave morbidity and mortality. Sleep and stroke have a definite intermingling neuropathological relationship, so along with expeditious acute management, efficient secondary prevention and consistent rehabilitation, sleep disorders' management has a hand in offering a medical service up to the mark. Objective: Screening of sleep disorders' prevalence in patients who survived a previous stroke by applying simple questionnaires and to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…We found significant associations between physical and mental health statuses and sleep disorders. A consistent high prevalence of sleep disorders was reported in chronically ill patients (Ibrahim and Wegdan 2011;Abd Elsadek et al 2019;Mansour et al 2020); however, many longitudinal reports indicated sleep disorders as a risk factor for physical and mental health problems, suggesting bidirectional associations of sleep disorders and health status (Alvaro et al 2013).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We found significant associations between physical and mental health statuses and sleep disorders. A consistent high prevalence of sleep disorders was reported in chronically ill patients (Ibrahim and Wegdan 2011;Abd Elsadek et al 2019;Mansour et al 2020); however, many longitudinal reports indicated sleep disorders as a risk factor for physical and mental health problems, suggesting bidirectional associations of sleep disorders and health status (Alvaro et al 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Unfortunately, there has been no study to determine the prevalence and correlates of poor sleep disorders in this large and vital sector of Egyptian society. The previous Egyptian studies investigated sleep disorders in small samples of students (Ismail 2017;Salama 2017) or chronically ill patients (Ibrahim and Wegdan 2011;Abd Elsadek et al 2019;Mansour et al 2020). Therefore, we aimed to estimate the prevalence and correlates of sleep disorders in Egyptian public officials using a large Egyptian sample of a joint bilateral project between Egypt and Japan .…”
Section: Introductionmentioning
confidence: 99%
“…Further, we excluded 927 studies by the exclusion criteria. Overall, 111 studies were retained for the full-text evaluation, and finally 26 studies were included in the meta-analysis ( Fig 2 ) [ 7 , 19 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…A significant portion of stroke patients, between 20% to 63%, exhibit various sleep abnormalities, including hypersomnia, insomnia, parasomnias, circadian rhythm problems, periodic limb movement disorder, and sleep-disordered breathing, according to research by Kernan et al (18) . Mansour et al (19) , demonstrated that 70.6% of people experienced sleep difficulties, this is unquestionably a major problem. 10.7% of people with 14.7% insomnia had it as a child.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally taken into consideration as predictors of the patient's sleep quality were daytime dysfunction, latency, and sleep duration. Additionally, Mansour et al (19) found that 17.3% of patients had severe EDS, including breathing disorders that interfere with sleep. Eight patients (10.6%) had a severe form of apnea, compared to 14 patients (18.7%) who had a moderate form.…”
Section: Discussionmentioning
confidence: 99%